Simultaneous Huge Splenic and Mesenteric Hydatid Cyst - Mostafa M. Abdelmaksoud; Alaa Jamjoom; Mohamed T. Hafez (Case Reports in Surgery)
Hydatid disease (HD) is caused by Echinococcus granulosus and is endemic in many parts of the world. This parasitic tapeworm can produce cysts in almost every organ of the body, with the liver and lung being the most frequently targeted organs. The spleen and mesentery are unusual locations. We report a case of simultaneous huge splenic and mesenteric hydatid cyst in a 91-year-old male patient. The patient was presented with chronic abdominal pain, increased frequency of defecation, and typical history of animal contact (cattle, sheep, and dogs). After performing imaging studies, he was diagnosed with a simultaneous huge spleen and pelvic mesentery hydatid cyst that was managed surgically by splenectomy, pelvic mesenteric cyst deroofing, and partial cystectomy.